On perturbative aspects of a nonminimal Lorentz-violating QED with CPT-even dimension-5 terms - T. Mariz; M. Melo; J. R. Nascimento; A. Yu. Petrov (European Physical Journal C: Particles and Fields, 2024)
Abstract In this paper, we explicitly calculate the lower CPT-even one-loop quantum corrections in nonminimal Lorentz-violating spinor QED with all possible CPT-even dimension-5 operators. Within our calculations, we restrict ourselves to the cases when these parameters are completely expressed in terms of one constant vector.